KONTRIBUSI DAN PENGARUH PAJAK RUMAH KOS TERHADAP PENDAPATAN ASLI DAERAH SETELAH PEMBERLAKUAN PERATURAN DAERAH KOTA KENDARI NOMOR 2 TAHUN 2011 - Irfan Ido (Universitas Halu Oleo, 2019)
Kendari City is the capital of Southeast Sulawesi Province which is a trade centre and centre for higher education. The function of the region triggered the migration of people from outside the Kendari City area to find employment and or continue their education to Higher Education.The movement of residents from outside the city implies a demand for a place to live. One alternative to the residence is the availability of boarding houses. Rental houses can contribute taxes based on Kendari City Regulation No. 2 of 2011 concerning rental house taxes. This study aims to analyze the Contribution and Effect of Housing Tax on Regional Original Revenue during the period 2012-2017 after the enactment of Kendari City Regional Regulation Number 2 of 2011 concerning Regional Taxes. The analysis technique uses descriptive statistics and simple regression using secondary data from Regional Original Income and Kendari City Tax Revenue. Research conclusions: (1) Contribution of rental house tax to Kendari's total original regional income in the very less category, (5) Rental house tax has a significant effect on Kendari's Original Regional Income. Keywords: Regional Regulation, Rental House Tax, Revenue